La naturaleza relacional del lenguaje revelada a través de casos anómalos y creativos - Gil, José María (Anales de Lingüística, 2025)
This article contrasts seven types of linguistic “marginal cases” through a relational perspective: misunderstandings, linguistic errors, conceptual errors, Freudian slips, unintended puns, intentional puns, and poetic creativity. Far from being accidental or peripheral, these phenomena reveal the structured and dynamic nature of language. Drawing on examples from English, Spanish, German, and Mapudungun, the analysis shows how phonological similarity, lexical salience, contextual conditions, and cultural background shape both intended meanings and miscommunication. While slips and errors expose the fragility of reference, poetic and playful uses highlight language’s power to create new conceptual links or even suspend oppositions. Errors and creativity thus emerge not as random accidents but as patterned outcomes of network processes that connect language, cognition, and culture. By situating the poles of error and creativity within a single framework, the article clarifies the difference between referential failure and deliberate invention. Ultimately, so-called marginal cases provide a privileged entry point into language, showing that communication is less a smooth transfer of information than a continuous process of activation and transformation within relational networks.